Bile acids supplementation modulates lipid metabolism, intestinal function, and cecal microbiota in geese - Li, Guangquan; Wang, Xianze; Liu, Yi; Gong, Shaoming; Yang, Yunzhou; Wang, Cui; Wang, Huiying; He, Daqian (Frontiers in Microbiology, 2023)
Bile acids(BAs) are important components of bile and play a significant role in fat metabolism. However, there is currently no systematic evaluation of the use of BAs as feed additives for geese.This study aimed to investigate the effects of adding BAs to goose feed on growth performance, lipid metabolism, intestinal morphology, mucosal barrier function, and cecal microbiota. A total of 168 28-day-old geese were randomly assigned to four treatment groups and fed diets supplemented with 0, 75, 150, or 300 mg/kg of BAs for 28 days. The addition of 75 and 150 mg/kg of BAs significantly improved the feed/gain (F/G) (p < 0.05).The addition of BAs decreased abdominal fat percentage and serum total cholesterol (TC) levels, with 150 mg/kg of BAs significantly reducing serum triglyceride levels and increased expression of Farnesoid X Receptor (FXR) mRNA in the liver(p < 0.05), 300 mg/kg of BAs significantly increasing the expression level of liver peroxisome proliferator-activated receptor α (PPARα) (p < 0.05). In terms of intestinal morphology and mucosal barrier function, 150 mg/kg of BAs significantly increased villus height (VH) and VH/crypt depth (CD) in the jejunum (p < 0.05). The addition of 150 and 300 mg/kg of BAs significantly reduced the CD in the ileum, while increasing VH and VH/CD (p<0.05). Additionally, the addition of 150 and 300 mg/kg of BAs significantly increased the expression levels of zonula occludens-1 (ZO-1) and occludin in the jejunum. Simultaneously 150mg/kg and 300mg/kg BAs increased the total short-chain fatty acids (SCFA) concentrations in the jejunum and cecum(p < 0.05).Supplementation with BAs resulted in a significant increase in the ɑ-diversity of cecal microbiota and a decrease in the abundance of Proteobacteria in the cecum. The addition of 150 mg/kg of BAs significantly reduced the abundance of Bacteroidetes and increased the abundance of Firmicutes. Moreover,Linear discriminant analysis Effect Size analysis (LEfSe) showed that the abundances of bacteria producing SCFA and bile salt hydrolases (BSH) were increased in the BAs-treated group. Furthermore, Spearman’s analysis showed that the genus Balutia, which is negatively correlated with visceral fat area, was positively correlated with serum high-density lipoprotein cholesterol (HDL-C), while Clostridium was positively correlated with intestinal VH and VH/CD. In conclusion, BAs can be considered an effective feed additive for geese, as they increased SCFA concentration, improve lipid metabolism and intestinal health by enhancing the intestinal mucosal barrier, improving intestinal morphology, and altering the cecal microbiota structure.